2019
DOI: 10.1007/s10014-019-00355-w
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell glioblastoma is a distinctive subtype of glioma characterized by vulnerability to DNA damage

Abstract: Giant cell glioblastoma (GC-GBM) consists of large cells with pleomorphic nuclei. As a contrast to GC-GBM, we defined monotonous small GBM (MS-GBM) as GBM that consists of small cells with monotonous small nuclei, and compared the DNA damage as well as other pathological features. GC-GBM showed minimal invasion (< 2 mm) and focal sarcomatous areas. TERTp was wild type in GC-GBM but mutant in MS-GBM. OLIG2 expression was significantly higher in MS-GBM (P < 0.01) (77% in MS-GBM and 7% in GC-GBM). GC-GBM showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“… 7 , 8 Furthermore, certain copy number variations that occur more frequently in conventional glioblastoma, such as EGFR amplification and CDKN2A homozygous deletions, are much less frequent or absent in gcGBM. 1 , 5 , 6 While gcGBMs have been shown to be vulnerable to DNA damage due to a higher propensity for DNA double strand breaks, 9 the underlying molecular mechanisms unique to gcGBM remain unknown.…”
mentioning
confidence: 99%
“… 7 , 8 Furthermore, certain copy number variations that occur more frequently in conventional glioblastoma, such as EGFR amplification and CDKN2A homozygous deletions, are much less frequent or absent in gcGBM. 1 , 5 , 6 While gcGBMs have been shown to be vulnerable to DNA damage due to a higher propensity for DNA double strand breaks, 9 the underlying molecular mechanisms unique to gcGBM remain unknown.…”
mentioning
confidence: 99%
“… 35 , 36) Furthermore, high CD133 expression is reported to be a useful predictor for GBM dissemination. 5 , 37) It was also reported that PTEN might be one of the suppressor factors in glioma cell dissemination, since PTEN mutation was significantly detected in malignant gliomas with meningeal gliomatosis. 38 , 39) However, PTEN mutation was not demonstrated in our case.…”
Section: Discussionmentioning
confidence: 99%
“…4) Giant cell glioblastoma (GCG) is an unusual GBM subtype defined by the latest classification of the World Health Organization. 5,6) GCG constitutes only 1% of adult GBMs and 3% of pediatric GBMs. 6,7) Although GCGs are diagnosed at relatively younger ages than the more common GBM, 7) they rarely develop in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…These cells, reminiscent of neuronal subtype, often display specific neuronal marker expression such as synaptophysin and MYC amplification. In GBM specimens, multinucleate giant cells and other packed rhomboid-like cells with abundant cytoplasm, probably derived from epithelium, have also been found [ 17 ]. The limitations of the classical histopathological diagnosis of GBM tumors, mainly due to broad intracellular variability, could be partially overcome by the aid of DNA methylation-based classification.…”
Section: Gbm Classificationmentioning
confidence: 99%
“…Many of the invasive mechanisms utilized by GSC were found to mimic NSC motility in white matter and blood vessels [ 16 ]. Interestingly, GBM tumors display an infiltrative leading edge that disseminates into healthy tissue and orthotopic xenograft tumors derived from human GSC mimic this invasive behavior displaying GSC concentrated at the tumor edge [ 17 ]. The reported GSC resistance to radiation and conventional chemotherapeutics, including temozolomide, are currently ascribed to a number of factors: signaling pathways involved in tumor cell contacts and tumor–stroma interactions, including the Wnt/β-catenin, the Notch, PI3K, and JAK/STAT pathways [ 17 ].…”
Section: Glioma Cells In 2d and 3d Modelsmentioning
confidence: 99%